Arabidopsis Serine Decarboxylase 1 (SDC1) in Phospholipid and Amino Acid Metabolism - Liu, Yu-chi; Gunawan, Farrel; Yunus, Ian Sofian; Nakamura, Yuki (Frontiers in Plant Science, 2018)
Arabidopsis thaliana serine decarboxylase 1 (SDC1) catalyzes conversion of serine to ethanolamine, the first reaction step of phosphatidylcholine and phosphatidylethanolamine biosynthesis. However, an involvement of SDC1 in amino acid metabolism remains elusive despite that serine is the substrate of SDC1. Here, we showed that SDC1 localizes in mitochondria although phosphatidylcholine and phosphatidylethanolamine are known to be produced in the ER. Moreover, we found that overexpression of SDC1 decreased levels of amino acid compounds derived from mitochondrial tricarboxylic acid cycle. These results suggest that mitochondria-localized SDC1 plays an important role in both phospholipid and amino acid metabolism in A. thaliana.